Fa'āliyat Istikhdam al Sūrah al Mutasalsilah li Tarqiyah Qudrat al Tulāb 'ala al Insa' bi al Ma'had daru al Falah - Salmah Nur; Putri Rahmawati (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
The effectiveness of the use of the serial image method to improve the ability of students (experimental research at the Nur Al-Falah Melabuh Islamic Boarding School Institute) Kitabah (writing skills) is a process of brain work in expressing the contents of the human mind. Insya' can help students express their thoughts in the correct written form. Some students at Maʼhad Nurul Falah Meulaboh are not able to compose simple sentences (number of mufidah) properly and correctly and they have difficulty in compiling these sentences. One of the factors that affect students' understanding difficulties and students' weak understanding insya' is caused by teachers who do not use appropriate media in learning. The purpose of this research is to determine the effectiveness of using strip drawing media in learning insya’ in Maʼhad Nurul Falah Meulaboh. The research method used in this research is the experimental method and to collect data, the researcher uses direct observation and test. . In terms of data analysis, the researcher used the T-Test formula. The results showed that the use of strip drawing media was effective in improving students' ability in learning insya' where the highest score after using strip drawing media reached 90 and this was also shown from the t-test score which was greater than the t-table score, which was 4.25 8.49.